2003
DOI: 10.1200/jco.2003.01.119
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function, Fatigue, and Menopausal Symptoms in Women Receiving Adjuvant Chemotherapy for Breast Cancer

Abstract: Adjuvant chemotherapy causes cognitive dysfunction, fatigue, and menopausal symptoms in women with breast cancer. Priority should be given to the study of strategies that might reduce these toxic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
217
0
13

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(245 citation statements)
references
References 38 publications
13
217
0
13
Order By: Relevance
“…However, the FACT-F includes a brief 13-item fatigue subscale that is more suitable for use in clinical trials. The FACT-F has been used to evaluate fatigue in patients with a variety of diagnoses receiving various treatments (Table 3) [35][36][37][38][39][40]. In each study, the majority of patients reported some degree of fatigue regardless of diagnosis or treatment modality.…”
Section: Multidimensional Toolsmentioning
confidence: 99%
“…However, the FACT-F includes a brief 13-item fatigue subscale that is more suitable for use in clinical trials. The FACT-F has been used to evaluate fatigue in patients with a variety of diagnoses receiving various treatments (Table 3) [35][36][37][38][39][40]. In each study, the majority of patients reported some degree of fatigue regardless of diagnosis or treatment modality.…”
Section: Multidimensional Toolsmentioning
confidence: 99%
“…Impairments in attention, mental flexibility, concentration, visual memory, and speed of information processing are estimated in some studies to occur in 4-75% of breast cancer patients who receive adjuvant chemotherapy and to persist even years after completion of the therapy (Ahles and Saykin 2002;Kingma et al 2001;O'Shaughnessy 2002;Schagen et al 1999Schagen et al , 2001Schagen et al , 2002aSchagen et al , b, 2006Silberfarb et al 1980;Tchen et al 2003;van Dam et al 1998;Wieneke and Dienst 1995). In these studies, the cognitive impairments are attributed to the chemotherapy but not to anxiety, depression, fatigue, self-reported complaints of cognitive dysfunction (Schagen et al 2006;Schagen et al 1999), patient age, or menopausal status (Brezden et al 2000).…”
mentioning
confidence: 99%
“…In 1995, in the first of a series of cross-sectional studies with early breast cancer patients, cognitive impairment was observed after cytostatic treatment in 75% of patients. 1 Although the results of subsequent cross-sectional trials assessing cognitive function during or after chemotherapy [2][3][4][5][6][7] were less dramatic, all of them reported substantial cognitive impairment rates of 16% to 50%, suggesting detrimental cytostatic side effects M.U. and R.K. receive research funding and honoraria from Bristol Myers Squibb and Amgen.…”
mentioning
confidence: 99%